(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2016)
The article aims to illustrate the results of the new policy of coca plants’ cultivation which Evo Morales – President of Bolivia since 2006 – has promoted at national and international level. The new framework distinguishes the use of the coca plant and its leaves between a legal and an illegal use. The former is linked to the local traditions and cultures and shall be therefore promoted and safeguarded. The latter concerns the exploitation of coca plant and leaves for illicit purposes and it is therefore banned and punished. Keywords: coca plants; coca leaves; Bolivia; Evo Morales; war on drugs